Anti-TNF-refractory colitis after checkpoint inhibitor therapy: Possible role of CMV-mediated immunopathogenesis - Lankes, Katharina; Hundorfean, Gheorghe; Harrer, Thomas; Pommer, Ansgar J.; Agaimy, Abbas; Angelovska, Irena; Tajmir-Riahi, Azadeh; Göhl, Jonas; Schuler, Gerold; Neurath, Markus; Hohenberger, Werner; Heinzerling, Lucie (OncoImmunology, 2016)
Immune-related adverse events (irAEs) induced by checkpoint inhibitors are well known. Since fatal outcomes have been reported early detection and adequate management are crucial. In particular, colitis is frequently observed and can result in intestinal perforation. This is the first report of an autoimmune colitis that was treated according to algorithms but became resistant due to a CMV reactivation. The 32-y-old male patient with metastatic melanoma treated within an anti-PD-1/ipilimumab combination study developed severe immune-mediated colitis (CTCAE grade 3) with up to 18 watery stools per day starting 2 weeks after treatment initiation. After improving upon therapy with immunosuppressive treatment (high dose steroids and infliximab) combined with parenteral nutrition diarrhea again exacerbated. Additionally, the patient had asymptomatic grade 3 CTCAE amylase and lipase elevation. Colitis was monitored by weekly endoscopies and colon biopsies were analyzed histologically with CMV staining, multi-epitope ligand cartography (MELC) and qRT-PCR for inflammatory genes. In the course, CMV reactivation was detected in the colon and treated with antiviral medication in parallel to a reduction of corticosteroids. Subsequently, symptoms improved. The patient showed a complete response for 2 y now including regression of bone metastases. CMV reactivation under checkpoint inhibitor therapy in combination with immunosuppressive treatment for autoimmune side effects has to be considered in these patients and if present treated. Potentially, CMV reactivation is underdiagnosed. Treatment algorithms should include CMV diagnostics.
EVALuna2:2063

Avoidance of complications in oncological surgery of the pelvic region : Combined oncosurgical and plastic reconstruction measures - Beier, Justus; Croner, R. S.; Lang, Werner; Arkudas, Andreas; Schmitz, Marweh; Göhl, Jonas; Hohenberger, Werner; Horch, Raymund E. (Chirurg, 2015)
Prevention of perioperative and postoperative complications resulting from surgical oncology in the pelvic region remains a major interdisciplinary challenge. With modern interdisciplinary concepts joining forces of various surgical specialties, tumor resection can be sufficiently carried out with wide margins and the patients benefit from reduced morbidity even in complex situations. As an example chronic fistulation and secretion from the presacral cavity and sinus may result as potential sequelae from intra-abdominal and intrapelvic tumor resection, especially when neoadjuvant multimodal therapies have been applied. This can be prevented by simultaneous transplantation of for example transpelvic vertical rectus abdominis myocutaneous (VRAM) flap transfer, while extensive perineal skin and soft tissue defects may also be simultaneously reconstructed. In cases of malignant soft tissue tumors in the pelvic region a staged surgical procedure can be performed with a period of time between tumor resection and reconstruction. Thus, a histological R0 status can be secured prior to plastic reconstruction surgery in order to increase oncological safety. In cases of postresectional exposition of e. g. pelvic or femoral vessels or intrapelvic and intra-abdominal organs simultaneous flap procedure is mandatory.The reconstructive armamentarium of the plastic surgeon should contain not only pedicled but also free microsurgical flaps so that no compromise in terms of the extent of the oncological resection has to be accepted. At the same time perioperative and postoperative complications may be avoided and the patient quality of life can be preserved even in more complex cases.
EVALuna2:15195

Distant metastases in colorectal carcinoma: A proposal for a new M1 subclassification - Merkel, Susanne; Weber, K.; Croner, R. S.; Golcher, H.; Göhl, Jonas; Agaimy, Abbas; Semrau, S.; Wein, Axel; Hohenberger, Werner; Wittekind, C.; Siebler, Jürgen (Ejso, 2016)
In 2010, the seventh Tumour-Node-Metastasis (TNM) cancer staging system of the International Union for Cancer Control (UICC) and the American Joint Committee of Cancer (AJCC) introduced a subdivision of M1 in the TNM classification of colorectal carcinomas. For the eighth TNM edition which will be released in the autumn of 2016 and will become effective in January 2017 new proposals are appreciated. The aim of our study was to define a new and better proposal for M1 subclassification.In a total of 814 patients with stage IV colorectal carcinoma treated between 1995 and 2013 prognostic factors were analysed in univariate and multivariate analyses.Advanced age, treatment in the earlier period 1995-2003, involvement of multiple metastatic sites, and non-curative resection were found to be independent prognostic factors. In patients with only one metastatic site, survival was good in patients with liver or lung metastasis, moderate in patients with metastasis of the peritoneum or non-regional lymph nodes and poor in patients with other rarely metastatic involved organs. The new proposal defines M1a, Metastasis confined to one organ: liver or lung (2-year survival 51.6%); M1b, Metastasis confined to one organ: peritoneum or non-regional lymph nodes, or Metastasis confined to liver plus lung (2-year survival 39.4%); and M1c, Metastasis confined to one organ: all other sites, or Metastasis in more than one organ, except liver plus lung (2-year survival 21.6%).The new proposal can identify three prognostic groups in stage IV colorectal carcinomas with significant differences in survival.
EVALuna2:2060

Old Age, nodular Melanoma, Tumor Thickness and Ulceration are Risk Factors for regional and systemic Metastases in Melanoma Patients after negative Sentinel Node Biopsy - Erdmann, M.; Dominik, S.; Göhl, Jonas; Grützmann, Robert; Schuler, Gerold; Schellerer, Vera (2017)
EVALuna2:15294

Oncological outcome after hyperthermic isolated limb perfusion for primarily unresectable versus locally recurrent soft tissue sarcoma of extremities - Vassos, N.; Brunner, Maximilian; Perrakis, A.; Göhl, Jonas; Grützmann, Robert; Hohenberger, Werner; Croner, R. S. (Surgical Oncology-Oxford, 2020)
Introduction: The management of locally advanced extremity soft tissue sarcomas, particularly in terms of a limb salvage strategy, represents a challenge, especially in recurrent tumors. In the context of a patient-tailored multimodal therapy, hyperthermic isolated limb perfusion (ILP) is a promising limb-saving treatment option. We report the outcome of patients with primarily irresectable and locally recurrent soft tissue sarcoma (STS) treated by ILP. Patients and methods: Data about patient demographics, clinical und histopathological characteristics, tumor response, morbidity and oncological outcome of all patients with STS, who underwent an ILP at our institution in a 10-year period, were retrospectively detected and analyzed. Results: The cohort comprised 30 patients. Two patients were treated with ILP for palliative tumor control, 13 patients because of a local recurrent soft tissue sarcoma (rSTS) and 15 patients because of primarily unresectable soft tissue sarcoma (puSTS). 25 of the 28 patients with curative intention received surgery after ILP (11 pts with rSTS and 14 pts with puSTS). Histopathologically we observed complete response in 6 patients (24%) and partial responses in 19 patients (76%) with a significant better remission in patients with puSTS (p = 0,043). Limb salvage rate was 75%. Mean follow-up was 69 months [range 13–142 months]. Seven (7/11; 64%) patients with rSTS and one (1/14; 7%) patient with puSTS developed local recurrence after ILP and surgery, whereas eight (8/13; 62%) rSTS patients and seven (7/15; 47%) puSTS patients developed distant metastasis. During follow-up, eight patients (28.5%) died of disease (5/13; 38%) rSTS and 3/15 (20%) puSTS. ILP in the group of previously irradiated sarcoma patients (n = 13) resulted in a limb salvage rate of 69% and was not associated in an increased risk for adverse events. Discussion: ILP for advanced extremity STS is a treatment option for both puSTS and rSTS resulting in good local control and should be considered in multimodal management. ILP is also a good option for patients after radiation history.
CRIS-Team Scopus Importer:2020-09-11
Keywords: Isolated limb perfusion; Recurrent; Soft tissue sarcoma

Prognosis of patients with colonic carcinoma before, during and after implementation of complete mesocolic excision - Merkel, Susanne; Weber, K.; Matzel, Klaus; Agaimy, Abbas; Göhl, Jonas; Hohenberger, Werner (British Journal of Surgery, 2016)
The implementation of complete mesocolic excision (CME) for colonic cancer was accompanied by other important changes, including more patients with early diagnosis by screening and the introduction of adjuvant chemotherapy in patients with stage III disease. The contribution of CME remains unclear.In this observational study, data from patients with stage I-III colonic carcinoma were analysed by comparing five time intervals: 1978-1984 (pre-CME), 1985-1994 (CME development), 1995-2002 (CME implementation), 2003-2009 (CME) and 2010-2014 (CME), with a special focus on indicators of process and outcome quality.During the observed periods, the median age of patients increased (from 65 to 67 years), there were more right-sided carcinomas (from 17·0 to 32·4 per cent), more stage I disease (from 14·0 to 27·7 per cent) and fewer patients with regional lymph node metastases (from 42·7 to 32·0 per cent). The proportion of patients with pN0 disease and at least 12 examined regional lymph nodes increased (from 84·8 to 100 per cent) as did the R0 resection rate (from 97·0 to 100 per cent). Overall morbidity increased, whereas the in-hospital mortality rate was stable (range 1·8-3·7 per cent). Use of adjuvant chemotherapy in stage III colonic carcinoma increased from 0 to 79 per cent. The improvement in outcome quality was more evident in stage III than in stage I-II tumours. In stage III, the 5-year locoregional recurrence rate decreased from 14·8 to 4·1 per cent (P = 0·046) and the 5-year cancer-related survival rate increased from 61·7 to 80·9 per cent (P = 0·010).With CME, the quality indicators of process and outcome quality improved, especially in stage III colonic carcinoma. Adjuvant chemotherapy in stage III and multidisciplinary approaches in patients with metachronous distant metastases contributed to further outcome improvement.
EVALuna2:6780

Prognostic subdivision of pT2 rectal carcinomas - Merkel, Susanne; Weber, Klaus; Brunner, Maximilian; Baecker, Justus; Agaimy, Abbas; Göhl, Jonas; Hohenberger, Werner; Schellerer, Vera; Grützmann, Robert (International Journal of Colorectal Disease, 2019)
Purpose The aim of the present study is to explore the prognostic impact of a subdivision of pT2 by the depth of invasion into the muscularis propria in rectal carcinomas.
CRIS-Team WoS Importer:2019-04-18

Proposal for a new M1 subclassification in colorectal carcinoma - Merkel, Susanne; Weber, K.; Croner, R.; Golcher, H.; Göhl, Jonas; Agaimy, Abbas; Semrau, S.; Wein, Axel; Hohenberger, Werner; Wittekind, C.; Siebler, Jürgen (2016)
EVALuna2:2176

Results of isolated limb perfusion for metastasized malignant melanoma - Schellerer, Vera; Frenger, Johannes; Merkel, Susanne; Göhl, Jonas; Kersting, Stephan; Grützmann, Robert; Erdmann, Michael; Förtsch, Thomas (Surgical Oncology-Oxford, 2021)
Background and objectives: Locoregional metastases are typical biological manifestations of advanced malignant melanomas. Treatment with hyperthermic isolated limb perfusion (HILP) should be considered in affected patients. In the present study, we have analyzed the results of HILPs performed in our department. Patients and methods: Eighty patients with locoregional metastases of the extremities received HILP at the Department of Surgery between January 2007 and December 2016. The mean follow-up was 38 months. Results: The study included 50 men and 30 women (mean age: 63 years). The median time between melanoma diagnosis and HILP was 25 months (range: 1–219 months). HILP was performed in curative (n = 45) and palliative (n = 35) intention. Seventy-five patients received a drug combination of melphalan/dactinomycin and five patients received a drug combination of melphalan/tumor necrosis factor-alpha. Remission rates were determined in 72 of 80 patients (90%) as follows: partial response n = 28, complete response n = 25, no response n = 19. Of the 25 patients with complete response, 13 patients developed a new tumor manifestation during follow-up (locoregional recurrences n = 4; distant metastases n = 3; both n = 6). The median overall survival rate was 33 months. Tumor stage influenced the survival rate significantly (p = 0.001). Patients with complete response showed a significantly better overall survival than patients with partial or no response (p = 0.016). Conclusion: HILP is an effective therapeutic option in patients with locoregional metastases. This procedure carries a certain risk of side effects and adverse events but overall results in good response rates. Therefore, HILP should be offered to selected patients based on an individual discussion, considering their health status and oncological prognosis.
CRIS-Team Scopus Importer:2021-05-21
Keywords: Hyperthermic isolated limb perfusion; In-transit metastases; Malignant melanoma; Recurrence; Survival

Risk Factors for Regional and Systemic Metastases in Patients with Sentinel Lymph Node-negative Melanoma - Erdmann, Michael; Sigler, Dominic; Uslu, Ugur; Göhl, Jonas; Grützmann, Robert; Schuler, Gerold; Schellerer, Vera (Anticancer Research, 2018)
BACKGROUND: Sentinel lymph node status is a strong prognostic factor in melanoma. However, up to 21% of sentinel lymph node-negative patients develop locoregional and distant metastases during follow-up. AIM: To analyze risk factors for locoregional and distant metastasis in patients with sentinel lymph node-negative melanoma. PATIENTS AND METHODS: A total of 545 patients underwent sentinel lymph node biopsy (SNB) between 2005 and 2013 at our hospital. Data for 449 patients with a negative SNB were analyzed regarding risk factors and development of metastases. Follow-up was performed until 2016. RESULTS: A total of 72 SNB-negative patients developed metastases, including 25 (34.7%) distant and 47 (63.3%) locoregional metastases. Locoregional metastases occurred earlier compared to distant metastases (with a mean of 24.2 and 23.5 months for regional lymph node and cutaneous metastases, respectively, vs. 31.4 months for distant metastases). Patients with metastases despite negative SNB had a greater tumor thickness (p=0.001), a higher rate of nodular melanoma (p=0.001), ulceration (p<0.001), and were older (p=0.05) compared to SNB-negative patients without subsequent metastases. Out of SNB-negative patients, 16% developed metastases. CONCLUSION: Close clinical follow-up including sonography of the draining lymph node region is mandatory for melanoma patients regardless of SNB status.
EVALuna2:203619

Survival analysis in rectal carcinoma after neoadjuvant chemoradiation: various methods with different results - Merkel, Susanne; Weber, Klaus; Göhl, Jonas; Agaimy, Abbas; Fietkau, Rainer; Hohenberger, Werner; Grützmann, Robert; Hermanek, Peter (International Journal of Colorectal Disease, 2017)
Survival is an important indicator of outcome quality in rectal carcinoma. The 5-year survival rate is the typical outcome measurement. In patients with neoadjuvant chemoradiation followed by curative surgery, 7 years of follow-up is recommended. Different methods of survival analysis lead to different results. Here, we compared four different methods.The data of 439 patients with rectal carcinoma treated with neoadjuvant chemoradiation followed by curative total mesorectal excision (TME) surgery between 1995 and 2010 were analysed. After stratifying by stage, relative survival (RS), cancer-related survival (CRS), overall survival (OS) and disease-free survival (DFS) were compared. In particular, the 3-year disease-free survival rate was compared to the 5- and 7-year overall survival rates.In the total cohort, the 5-year survival rates ranged from 90% (RS), over 84% (CRS) and 83% (OS) to 72% (DFS). Depending on the stage of disease, the differences between the 5-year survival rates varied between 10 and 32 percentage points. The differences were lowest in UICC stage y0 and highest in UICC stage yIV. The 3-year DFS-rate was always lower (worse) than the 5-year OS rate and higher (better) than the 7-year OS rate, with the exception of stage yIV.Comparisons of survival are only meaningful if the same methods are applied. The 3-year rate of DFS was always worse than the rate of 5-year OS. Therefore, the 3-year rate of DFS appears to be a useful surrogate indicator in rectal carcinoma treatment studies.
EVALuna2:6896

The impact of surgical quality on prognosis in patients undergoing rectal carcinoma surgery after preoperative chemoradiation - Kiehlmann, Marcus; Weber, Klaus; Göhl, Jonas; Fietkau, Rainer; Agaimy, Abbas; Hohenberger, Werner; Merkel, Susanne (International Journal of Colorectal Disease, 2016)
The aim of the study was to analyse the impact of surgical quality on the prognosis of rectal carcinoma patients who underwent preoperative long-term chemoradiation and TME surgery.In a total of 314 patients, four quality indicators, including plane of surgery, pathological circumferential resection margin (pCRM), intraoperative local tumour cell dissemination and anastomotic leakage, were analysed with respect to locoregional recurrence, distant metastasis and overall survival.In 260 (82.8 %) of the patients, all four quality indicators were fulfilled. In 30 (9.6 %) of the patients, at least one quality indicator was not fulfilled; in 24 (7.6 %) of the patients, the data were not complete. Locoregional recurrence was significantly increased in patients who underwent surgery in the muscularis propria plane, who had a pCRM <= 1 mm or who experienced local tumour cell dissemination. In patients who had at least one quality indicator that was not fulfilled (suboptimal surgical quality), the 5-year rate of locoregional recurrence in those patients was 23.1 % compared to 4.8 % in patients who underwent optimal surgery (P = 0.001). In multivariate analysis, suboptimal surgery (hazard ratio (HR) 3.9; P = 0.020), abdominoperineal excision (HR 4.7; P = 0.003) and poor regression of primary tumours (HR 8.5; P < 0.001) were identified as independent prognostic factors for locoregional recurrence. In contrast to type of surgical treatment, ypT, ypN and regression grade, the quality of surgery did not significantly influence distant metastasis or overall survival.Even after preoperative chemoradiation, the surgical quality still has a strong impact on local control in patients with rectal carcinoma.
EVALuna2:6711

The influence of tumour site on prognosis in metastatic colorectal carcinomas with primary tumour resection - Merkel, Susanne; Schellerer, Vera; Wein, Axel; Semrau, Sabine; Geppert, Carol-Immanuel; Göhl, Jonas; Hohenberger, Werner; Weber, Klaus; Grützmann, Robert (International Journal of Colorectal Disease, 2018)
PURPOSE: The aim of our study was to compare the characteristics and prognosis between right- and left-sided metastatic colorectal carcinomas. METHODS: Data from 937 patients with stage IV colorectal carcinomas (synchronous distant metastasis) who had a resection of the primary tumour between 1985 and 2014 were analysed. Carcinomas in the caecum to transverse colon were defined as right-sided (n = 250; 26.7%). They were compared to tumours located from the splenic flexure to the rectum categorised as left-sided (n = 687; 73.3%). RESULTS: In right-sided carcinomas, we observed significantly more female patients (50.8 vs 36.2%; p < 0.001), more unfavourable histological types (24.0 vs 8.6%; p < 0.001), more M1c carcinomas (metastases to the peritoneum ± others; 32.0 vs 14.4%; p < 0.001) and more emergencies (11.6 vs 7.1%; p = 0.029), while multimodal treatment was utilised in fewer patients (51.6 vs 63.8%; p = 0.001) and curative resections were less frequently (24.1 vs 35.4%; p = 0.002). Prognosis was significantly worse in patients with right-sided carcinomas (2-year-survival 27.2 vs 44.6%, p < 0.01). This difference was more pronounced after R2 resection (15.3 vs 29.7%; p < 0.001), than after macroscopic curative resection (2-year-survival 63.9 vs 71.9%; p = 0.106). In multivariate Cox regression analysis, tumour site was found to be an independent prognostic factor for overall survival (HR 1.2; 95% CI 1.0-1.5; p = 0.012). During the three 10-year periods, the prognosis improved equally in patients with right- and left-sided carcinomas, while the differences in survival remained identical. CONCLUSIONS: In a surgical patient cohort undergoing primary tumour resection, significant differences in prognosis were observed between patients with metastatic right- and left-sided colorectal carcinomas.
EVALuna2:35146